'Structural Reform' and the Problem of Socialist Strategy Today. Issue 1 (2nd January 2018) - Rooksby, Ed
Abstract : This paper begins with the observation that the left-wing movements that have enjoyed significant political advances in Europe recently share a broad strategic orientation. They seek, that is, to combine electoral and parliamentary activity on the one hand with extra-parliamentary mobilisation on the other. Crucially, these formations seek to utilise parliamentary channels to introduce radical reforms and thus a central component of their approach is to form a 'left government' within the institutions of the capitalist state. Despite the failure of Syriza in office I argue that the radical left has little option but to work with these ascendant left formations and attempt to radicalise them from within. I suggest that in order to do so the radical left must transcend the twin dead ends of reformism and Leninism and the historical strategic impasse bound up with the counter-position of these strategic poles. I argue that a strategic perspective elaborated by a minority current within Syriza provides useful resources for navigating a route beyond this impasse. I then show that this perspective can be further elaborated and refined by drawing on theoretical resources associated with the concept of 'structural reform' developed in the late 1960s and 1970s. I argue that the work of Nicos Poulantzas and André Gorz is especially useful in this regard.